Study of the effect of flow modifiers on the operation of Heglig-Port Sudan Pipeline - Mohyaldinn, M.E. (Asian Research Publishing Network, 2016)
In this paper, the effect of a flow improver (i.e. Pour Point Depressant) on the operation of Heglig-Port Sudan Pipeline has been studied. Two types of PPD, namely PPD 25J1 and PPD 25J2, have been used with different doses and different operation scenarios were presumed. For every scenario, the pressure required to transport the flowing fluid through the pipeline has been calculated and pressure transverse between pump stations has been established. The optimum scenario has been selected based on critical analysis of the operation cost at different operation scenarios and PPD concentrations. It has been found that the optimum operation scenario is obtained by adding the PPD type 25J1 to the flowing fluid at 500 PPM. Â© 2006-2016 Asian Research Publishing Network (ARPN).